Comparative and Competitive Advantages of Palm Oil in International Markets - Nuraini, Candra; Helbawanti, Octavia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to (1) Analyze the competitiveness of Indonesian cocoa butter exports in international markets based on comparative advantages. (2) Analyzing the competitiveness of Indonesian cocoa butter exports in the international market based on competitive advantages. The competitiveness of palm oil is analyzed in two ways: comparative advantage analysis and competitive advantage analysis. The approaches used in comparative advantage analysis are RCA, RSCA, and Product Mapping (RSCA and TBI). Meanwhile, the competitive advantage analysis uses the ECI approach. The competitiveness of Indonesian palm oil exports has a comparative advantage (RCA 54.15); based on Product Mapping analysis, Indonesian palm oil is in Group C, which means it has export specialization and has a comparative advantage. The ompetitiveness of Indonesian palm oil exports shows a competitive advantage or an upward trend; the value shows more than one (ECI 1.01).